DEVELOPMENT OF THE ULOS MODEL TO IMPROVE CULTURE AWARENESS OF PHYSICS EDUCATION STUDENTS - Sijabat, Apriani; Sauduran, Golda Novatrasio; Sinaga, Christa Voni Roulina; Sianipar, Julia (Universitas Labuhanbatu, 2025)
Purpose – This study aims to describe the development and implementation of the ULOS learning model as an innovation to enhance the love of culture among Physics Education students at Universitas HKBP Nommensen Pematangsiantar (UHKBPNP). The background of this study lies in the urgency to integrate local culture into science education, aiming to strengthen students' cultural identity, foster appreciation for traditional values, and develop positive character alongside academic competencies.Methodology – The research employed a research and development (R&D) design with a sample of 30 Physics Education students. The procedure followed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Instruments included validation sheets for experts, questionnaires for students’ responses, observation sheets for classroom implementation, and pre-test and post-test to measure changes in cultural appreciation. Data were analyzed quantitatively using descriptive statistics and N-gain scores, as well as qualitatively through reflective discussions.Findings – The results indicated that the ULOS model is valid, practical, and effective. Expert validation yielded an average score of 0.91 (very valid). The implementation significantly improved students’ love of culture, with effect size results in the medium to high category. Moreover, students demonstrated a greater awareness of integrating cultural elements into their learning and expressed stronger motivation to preserve local wisdom.Contribution – This study contributes to the enrichment of educational models by integrating ethnopedagogy into science learning. The ULOS model serves as a framework to cultivate cultural awareness and appreciation while simultaneously developing critical thinking skills. The study offers a practical guide for educators and researchers in designing culturally responsive learning models that support the sustainability of local heritage in higher education.